The ups and downs of Diplocraterion in the Glen Rose Formation (Lower Cretaceous), Dinosaur Valley State Park, Texas (USA). Issue 1 (2nd January 2016) - Martin, Anthony J.; Blair, Michael; Dattilo, Benjamin F.; Howald, Sadye; Farlow, James O.
Abstract : Diplocraterion, a U-shaped burrow attributed to infaunal invertebrates, is normally a shallow-marine trace fossil and not part of a continental vertebrate ichnoassemblage. Hence, the Glen Rose Formation (Aptian–Albian) of Texas (USA) presents an opportunity to study Diplocraterion associated with a world-class dinosaur tracksite. Most Diplocraterion are in a bioclastic wackestone–packstone bed just above the Taylor Tracklayer, a significant dinosaur track horizon. Diplocraterion are consistently sized, but with variable depths; most have protrusive spreiten and northeast–southwest trends. Smaller Arenicolites co-occur with Diplocraterion, and other trace fossils include Rhizocorallium and a large theropod trackway. Based on our analysis, a sea-level rise buried the Taylor Tracklayer, with a shallow-marine carbonate mud colonised by Diplocraterion and Arenicolites tracemakers. Protrusive Diplocraterion, eroded burrow tops, Rhizocorallium, and other criteria point towards firming and net erosion of the bed caused by a stillstand. The depositional environment of the Diplocraterion bed was possibly a subtidal lagoon that covered shoreward sediments impacted by large theropods. Burrow orientations suggest bidirectional currents consistent with trends of theropod trackways, implying each were controlled by a shoreline. The results of our study demonstrate how marine invertebrate and continental vertebrate trace fossils can be used together to define fine-scale changes in former carbonate shorelines.